The effects of cheerleading surfaces on ankle landing characteristics during vertical and flip landings - Nguyen, A. V.; Slavens, B. A.; Cobb, S. C.; O`Connor, K. M. (Journal of Applied Biomechanics, 2025)
Lateral ankle sprains are common in cheerleading, especially during tumbling. Landing surfaces influence injury risk by affecting joint mechanics, but few studies compare vertical and flip landings. This study examined the effects of a hard (HARD) and matted (MAT) surfaces on vertical drop (VERT) and flip (FLIP) landing tasks. Twelve collegiate cheerleaders performed both tasks with 3-dimensional kinematics and kinetics collected. Repeated-measures analyses of variance (task × surface, P < .05) analyzed sagittal and frontal plane variables. The FLIP task exhibited 84% greater peak ground reaction forces and 148% greater loading rates, as well as greater peak ankle angles and reduced ankle plantar flexion at initial contact compared to the VERT task. Increased foot velocities at initial contact during FLIP, driven by angular velocity, likely explained these heightened characteristics. HARD surface landings resulted in greater peak loading rates, peak angles, and inversion at initial contact. The peak plantar flexor moment was greater when landing on a HARD surface after a FLIP. Flip landings may elevate injury risks compared to vertical landings while supporting that harder landing surfaces increase injury risks. The significant differences between the tasks due to angular velocity differences also caution against generalizing vertical landings to landings within acrobatic sports.